05 Objective Violence and Symbolic Violence in Schools. Studies on the Perception of High-school Students - Elena BUJOREAN (Association of Social and Educational Innovation, 2016)
The data of our research examined the possibility of establishing some inter-conditioning between the symbolic violence and the level of objective violence found in schools. The indicators through which I have examined the level of symbolic violence (inequity, non-inclusive school environment, marginalization, authority in knowledge building) vary depending on the level of objective violence, which supports the hypothesis that symbolic violence enables physical (objective) violence among the groups of students.